Sociology as a Process: The Historical Interdependence of a Science, its Actors, and Society (KULT_online, 2010)
In his book Geschichte der Soziologie (History of Sociology) German sociologist Volker Kruse gives a concise overview of the development of sociology during the last two centuries (since 1820). He describes the complex interactions between individuals, institutions, and society over five epochs. Arguing that sociology as a science developed alongside its protagonists, he uses biographies and theories to elucidate many sociological classics in light of societal developments before, during, and after the Second World War.